The Progress and Trend of UAV Power Line Inspection: A Bibliome Trics-based Visualization Analysis - Meng, Bin; Lu, Na; Wang, Qingqi; Lin, Chen (Recent Advances in Electrical & Electronic Engineering, 2025)
BackgroundThe application of Unmanned Aerial Vehicle (UAV) is a major turning point in the history of power line inspection and is of increasing interest to a growing number of researchers.ObjectiveThis study aimed to clarify the research status, hotspots, and evolutionary trends of UAV power line inspection to help researchers understand the dynamic evolution of research topics and provide guidance for future research directions.Methods737 high-quality papers were collected from the Web of Science Core Collection (WoSCC) database from 2001 to 2023, and descriptive statistical analysis, cooperation network analysis, keyword co-occurrence analysis, keyword clustering analysis, and keyword citation burst analysis were conducted using VOSviewer and CiteSpace.ResultsThe popularity of research on UAV power line inspection is increasing, with an average annual growth rate of 26.33% in publications between 2001 and 2023. China (444 publications, 60.24%) and USA (77 publications, 10.45%) are the most prominent countries. However, the level of cooperation between different countries, academic institutions, and scholars is low. The research topics are wide-ranging and interdisciplinary, mainly focusing on 4 areas: fault detection and diagnosis, path planning, and the application of deep learning in intelligent inspection. The research hotspot and trend is the integration of artificial intelligence, deep learning, and modern information technology to achieve UAV autonomous intelligent inspection. Some of the challenges faced in the development of the field are also summarized, and possible solutions are proposed.ConclusionThis study provides a comprehensive and systematic review, and the results provide a quick overview of the research status, hotspots, and evolutionary trends.
Keywords: bibliometrics analysis